NON-CONFESSIONAL ASPECTS OF SELF-IDENTIFICATION LEADERS IN THE CONTEXT OF THE HISTORY OF KAZAKH AUTONOMY (Journal of history-rus, 2021)
The place of Tolstoyism at the beginning of the twentieth century in the Kazakh, identifying itself predominantly Muslim, environment is a page of history that is little studied today. The historiography of this topic reflects different methodological approaches in connection with the periods of interest of historians of different convictions to the issues of the influence of ethical teachings at critical stages in the development of societies. The publications of scientists, nevertheless, made it possible to compare the points of view on the spread of the ideas of Tolstoyism in the studied region with the adjacent regions of Russia and Central Asia. The goal is to find a logical connection between agrarian demands in the context of the sociopolitical realities of the land issue in the Russian Empire (A. Bukeikhanov), and the ethics of the Tolstoyans (S. Sadvokasov). The research methodology is since Russian historiography did not study the influence of Tolstoyism ideas on the worldview of the national intelligentsia of the Steppe Territory before the events of MarchOctober 1917. The specified facet of the formation of the views of Kazakh youth, who later joined the leaders of Alash, and then moved on to work in the bodies of Soviet power, has not yet been considered in the context of spiritual alternative searches. It turned out that the ideological searches of the Kazakh intelligentsia, regardless of class, nationality, and confessional affilia tion, at the beginning of the twentieth century were one of the types of passive social protest the regime. This manifested itself in the identity of the young S. Sadvokasov. The practical implementation of the conclusions of this study is to identify a paradox: the influence of nonMarxist teachings during the years of Soviet power coexisted with the ideology of communism and atheism in Kazakhstan.Key words: Russia, Kazakh Republic, Tolstoyism, Islam, Kazakhs, Sadvokasov Smagul, autonomy,Bukeikhanov, commune, agriculture, confessions.